Collaborative discourse during coteaching: A case study of one in-service teacher's growth. (June 2023) - Guise, Megan; Hegg, Sarah; O'Shea, Mark; Stauch, Nancy; Hoellwarth, Chance
Abstract: This qualitative case study conducted in the United States from 2017 to 2020 examines how one in-service teacher's (IST's) coteaching practice shifted when collaborating with three different pre-service teachers (PSTs) during clinical practice. Through the analysis of recorded planning/assessing sessions, the authors identified primary discourse patterns and stance embodied by the IST. Over three years, the IST's discourse changed, shifting positioning from that of leader to teacher educator to learner/collaborator. An increase in asking for input and decrease in justifying/explaining thinking indicated a collaborative stance. Implications for other TPPs interested in shifting an IST's coteaching practice are provided.